Heuristic Evaluation-Based User Interface Analysis and Redesign of the Talenesia Human Resource Information System Application - Amelia Anis Miranda; Astri Ghina (Journal Integration of Management Studies, 2025)
This study investigates the usability of the TALENESIA Human Resource Information System (HRIS) through Jakob Nielsen’s heuristic evaluation framework. The evaluation identified 34 usability issues, comprising five critical and 29 major problems. The most commonly violated heuristics included Visibility of System Status, Recognition Rather Than Recall, and Error Prevention, indicating significant barriers to user efficiency and satisfaction. To address these concerns, a series of interface redesigns was developed based on expert recommendations and user-centered design principles. The redesigned interfaces were subsequently validated through structured feedback sessions involving both usability experts and end users. The validation phase revealed that 85% of the proposed changes were fully approved, confirming the practical value of the improvements. These enhancements led to a more intuitive, responsive, and error-tolerant system experience for users. The study highlights the importance of heuristic evaluation as a diagnostic tool and demonstrates how iterative redesign—guided by usability principles—can significantly improve the effectiveness and user experience of HRIS platforms. Ultimately, the research offers both a methodological contribution to usability testing and practical insights for organizations seeking to optimize their digital HR systems.